2019
DOI: 10.1111/grow.12343
|View full text |Cite
|
Sign up to set email alerts
|

Regulating informality: Worker centers and collective action in day‐labor markets

Abstract: Day‐labor markets are characterized by chronic instability, low pay, and weak institutional protections against violations of labor standards. In the U.S., worker centers address these conditions through the operation of hiring halls that dispatch workers, set minimum wages, and redress wage theft. Surveys conducted in Seattle in 2012 and 2015 were used to evaluate wage rates, employment rates, and wage theft variables for workers at a worker center and those seeking employment at four informal hiring sites. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
4
11
0
Order By: Relevance
“…In neither Philadelphia nor Raleigh-Durham were all workers able to access and enact the practices we feature here: Some worked at sites where these practices had not emerged or where the workers were not in a position to combine the three components needed to create the basis for the worker power and job transformation we detail. Other studies help reinforce this point, noting that even with formal safety regulations in place in North Carolina, immigrant worker safety is not guaranteed and can vary tremendously across regions and types of projects (Theodore 2019). Moreover, the regulatory environment has changed considerably since we concluded our field research.…”
Section: Implications For Labor Standards Research and Regulatory Reformmentioning
confidence: 71%
See 2 more Smart Citations
“…In neither Philadelphia nor Raleigh-Durham were all workers able to access and enact the practices we feature here: Some worked at sites where these practices had not emerged or where the workers were not in a position to combine the three components needed to create the basis for the worker power and job transformation we detail. Other studies help reinforce this point, noting that even with formal safety regulations in place in North Carolina, immigrant worker safety is not guaranteed and can vary tremendously across regions and types of projects (Theodore 2019). Moreover, the regulatory environment has changed considerably since we concluded our field research.…”
Section: Implications For Labor Standards Research and Regulatory Reformmentioning
confidence: 71%
“…It has shifted the focus from the ways that regulators with top-down coercive powers enforce labor codes to more closely examine the ways in which regulatory actors use interactive and interpretive processes to change firm practices and influence organizational cultures (Piore 2011;. This research has drawn our attention in particular to the observation that campaigns to enforce workplace rights are most effective when they draw on organizational actors and institutional networks that may not typically be associated with enforcement, including regulatory bodies that manage international trade (Postnikov and Bastiaens 2014), labor unions (Milkman, Bloom, and Narro 2013;Milkman and Ott 2014;Theodore 2019), community organizations and worker centers (Fine 2006;Connell et al 2009;Theodore 2019), consumer groups (Bartley 2007;Locke 2013;Levy, Reinecke, and Manning 2016), and even, in the case of immigrant workers, consular staff (Bada and Gleeson 2015).…”
Section: The Missing Work In Labor Standards Scholarshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Overcoming these barriers will be challenging because the spaces in which LDLs work often lack health and safety protections and are places where workers must tolerate substandard work conditions. 65 , 66 Results from this study serve as a call to action for the U.S. Office of Safety and Health Administration (OSHA) to provide closer surveillance and regulate the worksites that employ LDLs. Additionally, OSHA does take a position on addressing SPBs; however, much of their emphasis put the responsibility of protecting oneself purely on the workers.…”
Section: Discussionmentioning
confidence: 99%
“…The NDLS, conducted more than fifteen years ago, found that the majority of day laborers were recent immigrants (60 percent had arrived within the past five years), with only 11 percent having lived in the United States for more than 20 years, anticipating that day labor was a temporary bridge to more stable employment (Valenzuela et al 2006, 18, 20). In contrast, more recent studies have observed increasing age profiles and time in the United States among foreign-born day laborers in various US cities (Crotty 2014; Organista, Arreola, and Neilands 2016; Theodore 2017, 2020; Boyas, Valera, and Ruiz 2019; Valdez et al 2019). Duration is largely treated as a control variable in these studies, rather than being explored theoretically.…”
Section: Introductionmentioning
confidence: 86%